Źródła filozofii Descartes’a w myśli św. Augustyna - Śliwiński, Tomasz (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2011)
In this article I analyze the similarities between St. Augustine's and Descartes' philosophy. In particular I consider their spiritual conceptions of mind, God, and cognition theory. The most important similarities between both thinkers concern the dualism of substances, cogito/dubito theory, and the conception of immortal human soul, like a thinking thing (res cogitans). Other similarities concern matter conceived as a theoretical construct of extension without thinking, cognition theory and mature knowledge, problems of falsehood and truth, theory of soul and senses perception, theory of mathematical eternal truths, the role of mathematics in nature description, their understanding the biological and spiritual points of view, the relation between human soul and body, limited human and unlimited intellect of God, intention and decision making, and also being and nothingness. The main feature presented in both theories is theocentrism and the role of God. Both conceptions belong to Christian Platonism, then have an anti-Aristotelian character, and can be considered as examples of the philosophy of mind.